Evaluasi Peformance Heat Recovery Steam Generator (B-9203 C) di Plant PT. Petra Arun Gas - Huzairi Ulfa (Jurnal Riset, Inovasi, Teknologi & Terapan, 2025)
Heat recovery steam generation is a water steam boiler type steam generator that utilizes heat energy from fuel gas or residual exhaust gas from a turbine which can produce saturated steam. The HRSG system consists of a boiler feed system, steam system and fuel system. The boiler feed system provides water requirements for HRSG automatically according to steam requirements. The economizer and boiler are found in the 92 HRSG (Heat Recovery Steam Generation) unit. The economizer functions as an initial heater for the Boiler Feed Water (BFW) before it enters the Boiler. The boiler functions as final heating for the Boiler Feed Water (BFW) after the heated water comes out of the Economizer .